PEMBENTUKAN KARAKTER ANAK DENGAN POLA ASUH DEMOKRATIS - Affan Yusra; Dinny Rahmayanty; Nuramita Mita; Erna Rahmawati Hatijah; Dwi Kurnia Sari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This article discusses the influence of democratic parenting on the formation of children's character, the aim of which is for us to know what impacts the application of democratic parenting has on children, both good and bad. The author uses the literature observation method to summarize the results from various references which are then differentiated based on the type of research from each source used as a reference. In this context, democratic parenting patterns have positive and negative impacts on the formation of children's character, positive impacts include tolerance, independence, superior personality, the ability to share, respect for differences, and an attitude of not imposing the will of others. The impact of democratic parenting on children's social and emotional development includes children's ability to make friends easily, be willing to collaborate, show independence, and be willing to share. ant role of democratic parenting in shaping children’s character in a positive way.